Technological, pedagogical, and content knowledge for technology integration: a systematic literature review - Muhammad Sofwan; Mohd Faiz Mohd Yaakob; Akhmad Habibi (Institute of Advanced Engineering and Science, 2024)
Many empirical studies used technological, pedagogical, and content knowledge (TPACK) to evaluate technology integration in education. However, systematic reviews on TPACK, related to technology integration in education are still limited, linked to the TPACK and technology integration issue. Therefore, this systematic literature reviews TPACK-based studies from 2010 to 2022, focusing on three topics: instruments to assess TPACK, TPACK domains’ inter-correlation, and TPACK relationships with technology integration. This systematic literature review implemented PRISMA (preferred reporting items for systematic reviews and meta-analyses). The study used Science Direct as a platform for articles’ search with three keywords, namely TPACK, preservice teacher; TPCK, preservice teacher; and TPACK, preservice teacher, technology integration. There were 28 articles reviewed. The findings informed 11 articles regarding scales to assess TPACK. There were nine articles reported TPACK domains’ intercorrelation and 10 articles informed TPACK relationships with technology integration. This study could significantly contribute to advancing knowledge regarding instruments to assess TPACK, TPACK factors inter-correlation, and TPACK and technology integration.